Sales and Marketing Strategies in The Marketplace by Businesses in Solo Raya - Aminudin Ma'ruf; Putri Maidina Fadila; Sausan Liski Aulia (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
Every human being buys and sells to meet their needs and desires, technological developments make it easy for everyone to do various jobs, especially in buying and selling activities. This study aims to examine the strategies used by business owners at Shopee to increase their sales and marketing. This study adopts qualitative research methods with data collection techniques used are interviews with several business actors at Shopee by asking questions through Google Forms. The results of this study are sales and marketing strategies carried out by business owners to encourage business growth, namely improving product quality, using advertisements, introducing products in detail to consumers, and maintaining service performance. In this study, several factors were found to support business actors selling on Shopee, namely a wide range, easy access, and a free shipping and payment system on the spot. The results of this research can be put forward by research implications that may be useful in the future by business actors at Shopee. This paper humbly attempted to be used as an additional reference for further studies with similar topics, namely sales and marketing strategies in the Shopee marketplace.